Filament-wound glass-fibre reinforced polymer composites: Potential applications for cross arm structure in transmission towers - Asyraf, M. R. M.; Ishak, M. R.; Syamsir, Agusril; Amir, A. L.; Nurazzi, N. M.; Norrrahim, M. N. F.; Asrofi, Mochamad; Rafidah, M.; Ilyas, R. A.; Rashid, Mohamad Zakir Abd; Razman, M. R. (Springer Nature, 2022)
This manuscript reviews previous literature on filament-wound polymer composites and their potential applications as cross arm structures in latticed transmission towers. The current trends of cross arms implement pultruded glass fibre-reinforced polymer composites without any additional configurations. However, extreme tropical climate and dynamic wind loads can cause a high risk of sudden failure due to creep, followed by laminate crack propagation, which can induce structural failure. Glass fibre-reinforced polymer composites are more resilient in corrosion resistance, strength, extreme conditions, and life serviceability according to previous literature. The composite can also function as a good insulator in lightning impulse strength of composite cross arms. It is suggested that the current cross arm design has to adopt core structure as reinforcement to the structure by using filament winding process for long-term structures. Hence, the composite structure can withstand extreme environmental conditions via the filament winding process. Thus, this manuscript is expected to deliver a state-of-art review on the manufacturing process, perspectives, and potential of filament-wounded composite as cross arms in transmission towers.